Research Note: Development of a reverse transcriptase recombinase-aided amplification method for detection of Parrot Borna Virus 4 - Yuhang Bai; Guixin Dong; Peng Zhang; Mengyue Dong; Jiaqian Rao; Qian Wang; Runlin Shao; Ruiheng Liu; Keyu Feng; Qingmei Xie; Xinheng Zhang (Poultry Science, 2024)
ABSTRACT: The Parrot Borna virus 4 (PaBV-4) is the primary causative agent of parrot developmental disorder (PDD), leading to symptoms such as bloating, undigested feed in stool, decreased appetite, diarrhea, and weight loss. Its impact on the parrot industry has been significant, therefore, it is imperative to develop a rapid detection method for PaBV-4. The detection of PaBV-4 was achieved through the development of an RT-RAA assay, which involved the design of specific probes and primers targeting the N gene. This method allows for detection at 41°C within 30 min and has a minimum detection threshold of 8.56 × 101 copies/μL. The RT-RAA method demonstrated specific detection of PaBV-4 without any cross-reactivity observed with H5N6, H7N9, H9N2 avian influenza virus, newcastle disease virus (NDV), avian infectious bronchitis virus (IBV) and Parrot Borna virus 2 (PaBV-2). The coefficient of variation for the 3 repeatability experiments was below 10%. Tissue samples from 28 suspected cases of PaBV related deaths in parrots were analyzed using both RT-RAA and RT-qPCR methods. The sensitivity and specificity of both methods were 100%, demonstrating perfect agreement between them as indicated by a kappa value of 1. In conclusion, this study created a RT-RAA method for PaBV-4 detection successfully.